2019
DOI: 10.1111/sms.13500
|View full text |Cite
|
Sign up to set email alerts
|

Objectively assessed vigorous physical activity and motor coordination are associated in 11‐year old children

Abstract: This cross‐sectional study examined the associations between gender, sports club (SC) participation, physical activity (PA), motor coordination (MQ) and object control skill (TC). 11 year‐old children (n = 477) wore accelerometers during seven consecutive days for the analysis of moderate PA (MPA) and vigorous PA (VPA). To detect motor competence (MC), children's motor coordination was measured using the KTK (MQ), and object control skill with throw‐and‐catch task (TC). Sports club (SC) status was obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Since previous studies have shown that vigorous physical activity may improve CRF (44), the absence of a significant association between slopes of MVPA and CRF in the low and moderate MC profiles may be due to a lack of vigorous physical activity. Blomqvist et al (45), for example, found that children with higher MC also showed relatively higher vigorous physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have shown that vigorous physical activity may improve CRF (44), the absence of a significant association between slopes of MVPA and CRF in the low and moderate MC profiles may be due to a lack of vigorous physical activity. Blomqvist et al (45), for example, found that children with higher MC also showed relatively higher vigorous physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, promoting the development of GMC has been considered a key strategy during childhood when the objective is to encourage health-related quality of life, including long-term obesity prevention [8] and the maintenance of cardiorespiratory fitness [9]. It has been found that GMC is 2 of 13 positively related to higher levels of physical fitness [10], increased moderate-to-vigorous physical activity [11], and aspects of children's psychological development, i.e., cognition and intelligence [12].…”
Section: Introductionmentioning
confidence: 99%